Acute Effects of Static vs. Ballistic Stretching on Strength and Muscular Fatigue Between Ballet Dancers and Resistance-Trained Women. Issue 11 (November 2016) - Lima, Camila D.; Brown, Lee E.; Wong, Megan A.; Leyva, Whitney D.; Pinto, Ronei S.; Cadore, Eduardo L.; Ruas, Cassio V.
Abstract : Abstract: Lima, CD, Brown, LE, Wong, MA, Leyva, WD, Pinto, RS, Cadore, EL, and Ruas, CV. Acute effects of static vs. ballistic stretching on strength and muscular fatigue between ballet dancers and resistance-trained women. J Strength Cond Res 30(11): 3220–3227, 2016—Stretching is used to increase joint range of motion, but the acute effects can decrease muscle strength. However, this may depend on the population or mode of stretching. The purpose of this study was to compare the acute effects of static vs. ballistic stretching on strength and muscular fatigue between ballet dancers and resistance-trained women. Fifteen resistance-trained women (age 23.8 ± 1.80 years, mass 67.47 ± 7.77 kg, height 168.30 ± 5.53 cm) and 12 ballet dancers (age 22.8 ± 3.04 years, mass 58.67 ± 5.65 kg, height 168.00 ± 7.69 cm) performed 5 days of testing. The first day was control (no stretching), whereas the other 4 days were static or ballistic stretching in a counterbalanced order. Range of motion, strength, and fatigue tests were also performed. Both groups demonstrated a significant decrease in hamstrings strength after static (102.71 ± 2.67 N·m) and ballistic stretching (99.49 ± 2.61 N·m) compared with control (113.059 ± 3.25 N·m), with no changes in quadriceps strength. For fatigue, only ballet dancers demonstrated a decrease from control (71.79 ± 4.88%) to ballistic (65.65 ± 8.19%), but no difference with static (65.01 ± 12.29%). These findings suggest that stretching decreases hamstrings strength similarly in ballet dancers and resistance-trained women, with no differences between modes of stretching. However, ballistic stretching only decreased muscular fatigue in ballet dancers, but not in resistance-trained women. Therefore, no stretching should be performed before strength performance. However, ballistic stretching may decrease acute muscular fatigue in ballet dancers.